The Evolution of Public Debt Vulnerabilities In Lower Income Economies. (Policy Papers; Policy Paper, 2020)
Public debt in lower-income economies (LIEs) has risen in recent years, with half of the countries covered in this report now assessed to be at high risk of or already in debt distress.